A metal-drug self-delivery nanomedicine alleviates tumor immunosuppression to potentiate synergistic chemo/chemodynamic therapy against hepatocellular carcinoma - Chen Guo; Rui Dou; Linbang Wang; Jiayu Zhang; Xiaomeng Cai; Jiaruo Tang; Zhengyuan Huang; Xiaoguang Liu; Jun Chen; Hanqing Chen (Fundamental Research)
ABSTRACT: Hepatocellular carcinoma (HCC) is the most common primary liver cancer with a poor prognosis. Chemotherapy is one of the first-line clinical therapeutic strategies for HCC. Still, the effectiveness of chemotherapy is hampered by the tumor immunosuppressive microenvironment and drug resistance caused by insufficient delivery. Herein, we developed a metal-drug self-delivery nanomedicine (FDAH) to improve the chemo/chemodynamic therapeutic efficacy of HCC. The core of FDAH is an iron-based nanoparticle chelated with two clinical drugs, Doxorubicin (DOX) and Plerixafor (AMD3100). Additionally, the nanomedicine is externally modified with a hyaluronic acid (HA) shell, which can prolong the circulation time of the nanoparticles in the bloodstream after intravenous administration. After entering the bloodstream, the nanomedicine reaches the tumor tissue through the EPR effect and is phagocytosed by the tumor cells via HA/CD44-specific interaction. Iron ion-mediated chemodynamic therapy is mediated by the Fenton reaction to generate ROS, causing an imbalance of redox homeostasis within the tumor cells and enhancing the sensitivity of tumor cells to DOX. In addition, AMD3100 intervenes in the CXCL12/CXCR4 axis to influence the infiltration level of immune cells and promote DOX chemotherapy in tumor cells. This work suggests that alleviating immunosuppression via a metal-drug self-delivery system of the CXCR4 inhibitor can effectively improve the DOX chemotherapy and iron ions-mediated chemodynamic therapy.